Antioxidant and Cytotoxic Potential of Ethyl Acetate Fraction of Gandaria Stem Bark (Bouea macrophylla) Against MCF-7 Cell Line - Situmeang, Boima; Primawati, Junia Salsha; Oktafiani, Ismi; Musa, Weny JA; Kilo, Ahmad Kadir (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The stem bark of Bouea macrophylla (gandaria) represents a promising subject for further scientific investigation. Previous studies have reported that the bark contains high concentrations of total phenolic and flavonoid compounds, associated with potent antioxidant activity. This study evaluates the antioxidant and cytotoxic potential of the ethyl acetate fraction of B. macrophylla stem bark. Antioxidant activity was assessed using the DPPH and ABTS radical scavenging methods, while cytotoxic activity against MCF-7 breast cancer cells was determined using the MTT assay. The ethyl acetate fraction exhibited strong antioxidant activity with IC₅₀ values of 5.837 ± 0.060 ppm (DPPH) and 9.645 ± 0.697 ppm (ABTS). The cytotoxicity assay revealed an IC₅₀ value of 99.55 ppm, indicating moderate cytotoxic potential. These findings suggest that the ethyl acetate fraction of B. macrophylla stem bark possesses significant antioxidant activity and potential anticancer properties, supporting its possible application in natural therapeutic development.